Pathobiological properties of the ubiquitin ligase Nedd4L in melanoma. Issue 1 (31st October 2013) - Kito, Yusuke; Bai, Juncheng; Goto, Naoe; Okubo, Hiroshi; Adachi, Yoshihiro; Nagayama, Tomoko; Takeuchi, Tamotsu
Summary A recent global gene expression profiling study unexpectedly showed that activated oncogenic NRAS may recruit neural precursor cell expressed, developmentally downregulated 4L (Nedd4L; a human homologue of Nedd4‐2) in cultured melanoma cells. However, whether Nedd4L was expressed in melanoma tissues or participated in melanoma carcinogenesis remains to be clarified. Here, we investigated the expression status of Nedd4L in human melanocytes, benign nevi and melanoma tissue specimens and subsequently attempted to determine the role of Nedd4L in melanoma cell growth. Immunohistochemical staining revealed that Nedd4L was not present in any non‐tumorous melanocytes or in 18 benign nevi tissues, but it was detected in 34 of 79 cutaneous melanomas and 9 of 32 nodal metastatic melanomas. Downregulation of Nedd4L significantly reduced the growth of cultured G361 melanoma cells in vitro. Moreover, exogenous Nedd4L expression significantly promoted the growth of A2058 melanoma cells in vivo in a xenograft assay. The present findings indicate that Nedd4L expression may be increased to facilitate tumour growth in many melanomas.